2020
DOI: 10.1186/s13046-020-1521-4
|View full text |Cite|
|
Sign up to set email alerts
|

Musashi2 promotes EGF-induced EMT in pancreatic cancer via ZEB1-ERK/MAPK signaling

Abstract: Background: Our previous study showed Musashi2 (MSI2) promoted chemotherapy resistance and pernicious biology of pancreatic cancer (PC) by down-regulating Numb and p53. We further explored the novel molecular mechanism involving its oncogenic role in PC development. Methods: We investigated the potential role and mechanism of MSI2 in EGF-induced EMT in PC in vitro and vivo. Results: EGF enhanced EGFR (epidermal growth factor receptor) phosphorylation, induced EMT and activated ZEB1-ERK/MAPK signaling in 2 PC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 45 publications
2
67
0
Order By: Relevance
“…ERK signaling pathway will be activated as ROS increases, which finally promote the growth and metastasis of pancreatic cancer [38], therefore we put more attention on the ERK signaling pathway. It has been indicated that ERK signaling pathway can not only promote cell proliferation, apoptosis and metastasis but also induce EMT [39][40][41]. Therefore, we speculated that ABCA8 induces oxidative stress and ROS production through intracellular accumulation of cholesterol, which then induces EMT through the activation of ERK signaling pathway and facilitates the growth and metastasis of HCC cells.…”
Section: Discussionmentioning
confidence: 93%
“…ERK signaling pathway will be activated as ROS increases, which finally promote the growth and metastasis of pancreatic cancer [38], therefore we put more attention on the ERK signaling pathway. It has been indicated that ERK signaling pathway can not only promote cell proliferation, apoptosis and metastasis but also induce EMT [39][40][41]. Therefore, we speculated that ABCA8 induces oxidative stress and ROS production through intracellular accumulation of cholesterol, which then induces EMT through the activation of ERK signaling pathway and facilitates the growth and metastasis of HCC cells.…”
Section: Discussionmentioning
confidence: 93%
“…TGF-β1 activates ERK signaling, which is required for TGF-β1-mediated EMT in vitro 63 . Musashi2 promotes EGFinduced EMT in PC via ZEB1-ERK/MAPK signaling 64 . Taken together, CRT silencing inhibited TG-induced acute ERS and EMT via regulating Slug and ERK signaling in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cell invasion and migration are multistep processes which are nely regulated [20][21][22]. The epithelial-to-mesenchymal transition (EMT) has been identi ed as an important process of tumor cell invasion and migration [23][24][25]. Therefore, we determined the effects of PNN on EMT in prostate cancer cell.…”
Section: Pnn Over-expression Induces Prostate Cancer Cell Emtmentioning
confidence: 99%